The Exogenous Application of Malic Acid Eliminates Cadmium Concentrations in Aromatic Rice of Pulu Mandoti Emas Variety - Meriem, Selis; Aris, Nur Armiah; Nur, Fatmawati (LenteraBio : Berkala Ilmiah Biologi, 2025)
Food security and human health are at risk due to rice fields' heavy metal cadmium (Cd) pollution, which has become a global problem. As rice is a significant crop in Indonesia, reducing the detrimental effects of Cd accumulation in rice plants requires serious consideration. This study aimed to evaluate the effect of malic acid on the availability and uptake of Cd (in soil, roots, and shoots), the relative water content (RWC), the morphological growth, and the anatomical structure of roots in the local aromatic rice of the Pulu Mandoti Emas (PME) variety. The concentrations of Cd (CdCl2), comprising control (C1) and 10 mg/kg Cd (C2), and malic acid (C4H6O5), which included control (M1) and 50 µM malic acid (C2), were employed in this study. The results showed that Cd was only detected in the C2M1 at levels of 0.05 ppm in the soil and 4.47 ppm in the roots. The C2M2 eliminated Cd contents in the soil, roots, and shoots and further showed the highest values ​​for the RWC (69%), root length (12.51 cm), and root fresh weight (4.74 g) compared to other treatments. Anatomically, the C2M2 maintained the structural integrity of the root tissue, while the C2M1 disrupted the cortex tissue. The use of malic acid is recommended to preserve water potential and plant growth, as well as protect root anatomy under Cd exposure.